Jan Greshoff se ‘aanval’ op Olga Kirsch as een van die hoofredes vir haar emigrasie: ’n Psigoanalitiese beskouing / Jan Greshoff’s ‘Attack’ on Olga Kirsch as One of the Main Causes of Her Emigration: A Psychoanalytical Point of View - Minnaar, Thomas (Werkwinkel, 2014)
The poet Olga Kirsch left South Africa permanently for Israel in 1948. It is evident from her poetry that her Zionism, opposition to the racism of the National Party and a failed love played a role in her decision. This article focuses on another reason - a public attack by the Dutch critic Jan Greshoff in an Afrikaans literary magazine in 1946. Using concepts from psychoanalytical theories around borderline and narcissistic personalities, as well as the effect of emigration, Kirsch’s actions are examined as a reaction to narcissistic wounding. Investigating Greshoff’s criticism gives insights into the poet’s actions and explains the hiatus before she started publishing again in Afrikaans from 1971. It is stated that the poet is not considered to be a narcissist as her oeuvre is a testimony to her empathy with others, but the healthy narcissism needed in building one’s self-esteem underwent a severe blow when Kirsch lost the man she loved and was humiliated so devastatingly by the great Dutch critic.